Konservasi Musuh Alami Melalui Pemanfaatan Gulma dan Tanaman Refugia di Perkebunan Kelapa Sawit - Rahim, Abdul; Hidayah, Andi Ikhsan; Faizal, Faizal; Murtilaksono, Aditya (Agrosains : Jurnal Penelitian Agronomi, 2024)
The refugia and weeds have the potential as media for the conservation of natural enemies in oil palm plantations. The research aimed to compare the composition of natural enemies in plots of weeds and refugia plants' presence. Experiment one factor in a randomized block design (RCBD), which consisted of, (1) weed plots without refugia plants, (2) weeds and cosmos flowers, (3) weeds and zinnia flowers, and (4) weeds, cosmos, and zinnia flowers. Each treatment was repeated 4 times which were totally 16 experimental plots. The data were the species and the number of individual arthropods. In addition, it calculated the sum dominance ratio (SDR) of weeds, and the number and color of flowers. Data were analyzed descriptive, fisher's exact test (anova), duncan multiple range test (DMRT). Then, regression and correlation analysis for the relationship between the number of individual and flowers. The composition arthropod consisted of 5 Orders, 11 Families, and 14 Species. The species spider Bathyphantes nigrinus and insect Cosmolestes picticep are the dominant predator. There was no difference in the number of natural enemy species. However, there were differences number individuals in the plots of the combination of weeds and cosmos plants with weeds combined with zinnia flowers. Furthermore, the higher the number of flowers, the higher the number of individuals found at the observation site. The results of this study indicate that weeds and cosmos flowers are the best combinations for conserving natural enemies in oil palm plantations.